ANALISIS YURIDIS PENERAPAN KHI DALAM PENGGANTIAN TEMPAT AHLI WARIS/ AHLI WARIS PENGGANTI PADA MASYARAKAT KECAMATAN BANDA SAKTI KOTA LHOKSEUMAWE - DEWI KEMALASARI (PREMISE LAW JURNAL, 2015)
Legal regulation on Substitute Heir/Heir Replacement in Indonesia is regulated in Article 185 of in the Islamic Law Compilation. But, in fact, due to several reasons, not all of the community members of Banda Sakti Subdistrict, the City of Lhokseumawe has used the Islamic Law Compilation. The issuess raised in this study were how the concept of Substitute Heir/Heir Replacement is understood in Islamic Inheritance Law, how the Islamic Law Compilation was applied in the community members of Banda Sakti Subdistrict, the City of Lhokseumawe, and what constraints were faced in the application of the Islamic Law Compilation in relation to the case of Substitute Heir/Heir Replacement in Banda Sakti Subdistrict, the City of Lhokseumawe. This descriptive analytical study with empirical/sociological juridical approach was to answer the issues raised with effective consideration by studying the validity and invalidity of a rule of law influenced by various factors such as such as changes in the community, cultural developments, and so forth. Keywords: Islamic Inheritance Law, Islamic Law Compilation